Influence Of Carrier-Based Microbial Consortia On The Growth And Yield Attributes Of Sorghum [Sorghum bicolor (L.) Moench] (Applied Biological Research, 2020)
Pot experiments were conducted under greenhouse conditions at ARS,  ANGRAU, Amaravathi (India) during kharif 2018-19 to assess the effect of  carrier-based microbial consortia on the growth and yield of sorghum cv.  ‘CSV-27’. Two microbial consortia (MC1 = Azospirillium + P-solubilizer +  K-releaser + Zn-solubilizer + PGPR isolate; and MC2 = Azotobacter + Azospirillium + P-solubilizer + K-releaser + Zn-solubilizer + PGPR isolate) were evaluated along with different doses of inorganic fertilizers. Crop growth attributes like plant height, shoot length, shoot weight, root weight, nutrient uptake, weight of ear head, grains ear head-1, grain yield and stover yield were assessed. The treatment 75% recommended fertilizer dose + MC2  + FYM proved superior over all other treatments tested and gave significantly higher yield than other treatments. The use of biofertilizer consortia along with reduced dose of inorganic fertilizer are advised for successful sorghum growth.
Keywords: Microbial consortia; sorghum; growth attributes; yield attributes; fertilizers